Analisis Supervisi Pendidikan Untuk Pengembangan Profesionalitas Guru Berkelanjutan - Michelle Supit; Joulanda A.M Rawis; Mozes Markus Wullur; Viktory N.J. Rotty (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2021)
The quality of learning in Indonesia is indicated to have not met the expected quality. This has an impact on student learning achievement which is not yet encouraging, especially compared to student learning achievement. This study aims to analyze educational supervision for continuous teacher professional development. The method used is descriptive qualitative method. This research uses qualitative methods. Bogdan and Taylor in Moleong (2010:4) explain that qualitative research is